N or M? : a Tommy and Tuppence mystery - Christie, Agatha, 1890-1976 (Christie, Agatha, 1890-1976. Tommy and Tuppence mystery., 2024)
"It is World War II, and while the RAF struggles to keep the Luftwaffe at bay, Britain faces an even more sinister threat from 'the enemy within'--Nazis posing as ordinary citizens. With pressure mounting, the intelligence service appoints two unlikely spies, Tommy and Tuppence Beresford. Their mission: to seek out a man and a woman from among the colorful guests at Sans Souci, a seaside hotel. But this assignment is no stroll along the promenade--N and M have just murdered Britain's finest agent and no one at all can be trusted ..."--Page 4 of cover.